FIRST GENERATION OF NURSES TRAINED IN MAGALLANES, CHILE: ELEMENTS OF THEIR PROFESSIONAL IDENTITY - Barrientos, Helena Pinochet; Padilha, Maria Itayra; Teodósio, Sheila Saint-Clair da Silva (My University, 2020)
ABSTRACT Objective: to know the main elements of the construction of the professional identity in the first generation of graduated students from the Nursing course in Magallanes, from 1972 to 1976. Method: a historical research study with a qualitative approach, where the five graduated students from the first generation and a woman professor constitute the main source for reconstructing the past through oral thematic history. Data collection was performed by means of a semi-structured interview. The collected data were organized with the help of the Atlas Ti® program, then performing thematic content analysis based on Claude Dubar's concepts on identity types. Results: there are elements present in Dubar's exposition, such as the identities as an individual nurse and as a social nurse, whose constructions actually start prior to the beginning of the academic training in order to shape a new identity through successive reconstruction processes during the whole curricular process; however, in this group the importance of the faculty of that time stands out as a fundamental element in the construction of identities. Conclusion: the importance is evidenced of the identity projected by the professors in charge of the academic, theoretical, practical, and value-related activities, since they will model the identity the students will build when exiting their classrooms, reason why those who direct the training of the future nurses must consider both the historical and social moment of the generation being trained, as well as the competences, values, and own identities of those who train them.
Keywords: history; nursing; history of nursing; profession selection; nursing education; professional identity; social identification